Transduction of methicillin resistance in Staphylococcus aureus: recipient effectiveness and beta-lactamase production. - Stewart, G C (1980)
The effectiveness of Staphylococcus aureus strain 8325-4 as a recipient for the transduction of methicillin resistance requires the presence of a penicillinase plasmid but was found to be independent of the lysogenic state of the recipient. Effectiveness is conferred by the plasmid in either the autonomous or integrated states, although the transduction rate is higher in the former. Once established, the maintenance and expression of methicillin resistance were independent of continued carriage of the plasmid deoxyribonucleic acid. Analysis of penicillinase plasmid mutants indicated that beta-lactamase production was the plasmid function responsible for recipient effectiveness. Supportive evidence included the abrogation of recipient effectiveness by the beta-lactamase inhibitor clavulanic acid and the elimination of a plasmid requirement with recipient strains carrying a chromosomal beta-lactamase determinant. A possible role for beta-lactamase production in the transduction of methicillin resistance is discussed.